Hypoproteinemia as a prognostic risk factor for arteriovenous fistula failure. Issue 1 (29th January 2017) - Premuzic, Vedran; Hudolin, Tvrtko; Pasini, Josip; Zimak, Zoran; Hauptman, Dinko; Jelakovic, Bojan; Kastelan, Zeljko
Abstract: Introduction: Any vascular access is of limited duration with many factors which influence survival in patients on chronic hemodialysis (HD). Hypoproteinemia as a marker of chronic illness is common among chronic HD patients. Our aim was to analyze the survival of the primary arteriovenous fistula (AVFs) and the risk factors which influence their patency and to test the hypothesis that patients with normal values of serum proteins have lower risk of AVF failure compared to patients with hypoproteinemia. Methods: Seven hundred thirty‐four consecutive patients were included who underwent creation of an AVF. The patients were prospectively followed‐up for 2 years. Only patients with AVF function after a month from its creation were analyzed. The patients were divided into two subgroups, with normal and low serum protein levels (<65 g/L). Findings: At follow‐up 497 (67.7%) AVFs were still functional while 237 (32.3%) AVFs failed due to thrombosis or stenosis. Serum proteins and AVFs created on the forearm were positive predictors while diabetes was a negative predictor of longer AVF survival (P < 0.001; P = 0.003; P = 0.043). When comparing patients with normal and low serum protein levels (<65 g/L), mean survival time was significantly longer in patients with normal serum levels (P < 0.001). Discussion: In this study, hypoproteinemia was an independent prognostic marker for AVF failure at 2 years. Hypoproteinemia, based on our results, is an independent, more sensitive and prognostic marker of possible vascular access failure than the presence of other common factors which influence shorter AVF survival.